PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE GLOBAL PADA ANAK TUNAGRAHITA RINGAN - MEGA GUSTINA Putri (Jurnal Penelitian Pendidikan Khusus, 2016)
The background of the research is by a problem of children who have disability to read at IV/C grade. It can be seen from the observation that the children have troubled to read words wich mixed consonant letters. Based on the problem,the research has purpose to prove the global method would increase the early reading skill to minor illiterate children of IV/C grade at SLB Bina Nagari Tarusan. The research used experimental design with single subject research (SSR) method, with A B variable and technic of data analysis by visual graphic. Subject of the tesearch is illiterate children at IV C grade, they were asked to read one till three words for 10 exercises on each time of observate. The assesment of the research by write down the data that is correct. The variable measurement is within percentage. Baseline (A) condition used 7 times with mean level 28% and intervension (B) condition used 8 times with mean level 60%. The data analysis of inter and intra conditions have tendency of approximate estimation, stability tendency, data tracked and changing level which showed positive impact to the increasing of ability in early reading skill. Overlap data at the analysis of intra condition at baseline (A) and intervention (B) is 12,5%. It shows that more smaller percentage overlap will give better impact of intervention to target changing behaviors in the research. Based on the data, it proves that global method would increase the early reading skill to minor illiterate children of IV C grade at SLB Bina Nagari Tarusan.